2022
DOI: 10.3389/fnut.2022.874721
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning to sustainable healthy diets: A model-based and conceptual system thinking approach to optimized sustainable diet concepts in the United States

Abstract: Food production and consumption are essential in human existence, yet they are implicated in the high occurrences of preventable chronic diseases and environmental degradation. Although healthy food may not necessarily be sustainable and vice versa, there is an opportunity to make our food both healthy and sustainable. Attempts have been made to conceptualize how sustainable healthy food may be produced and consumed; however, available data suggest a rise in the prevalence of health-related and negative enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 40 publications
2
5
0
Order By: Relevance
“…Plant-based food is considered environmentally friendly and better for animal welfare than conventional analogs. The shift to a sustainable plant-based diet might significantly reduce total GHG emissions, land use, water consumption and energy use [160]. This finding corroborates studies that revealed that replacing animal-origin foods with plant-based foods might reduce food-related greenhouse gas emissions.…”
Section: Discussionsupporting
confidence: 83%
“…Plant-based food is considered environmentally friendly and better for animal welfare than conventional analogs. The shift to a sustainable plant-based diet might significantly reduce total GHG emissions, land use, water consumption and energy use [160]. This finding corroborates studies that revealed that replacing animal-origin foods with plant-based foods might reduce food-related greenhouse gas emissions.…”
Section: Discussionsupporting
confidence: 83%
“…The relationship between nutrient density and cost is well established, with numerous studies demonstrating that nutrient-dense foods and diets tend to be more expensive [30,42,43] yet also have a lower environmental impact [20,21,25]. The substantial positive correlation between nutrient density and cost, along with the significant negative correlation between nutrient density and environmental impact, aligns with patterns observed in the existing literature [25,42,43].…”
Section: Discussionsupporting
confidence: 72%
“…Many studies have analyzed two dimensions of sustainable diets [6,[18][19][20][21][22][23][24], with fewer studies including three [25][26][27][28][29] and even fewer measuring all four [30,31]. It is key to consider that the amount of greenhouse gas emissions is often the only measurement of environmental impact explored in these studies [19,20,27,28,30,31].…”
Section: Sustainable Foodsmentioning
confidence: 99%
“…Improving the health of CLWH (and HUU) is very important. One possible avenue is dietary interventions, which can be very successful short-term, but are not largely sustainable over time ( 73 , 74 ). Food and nutrition literacy should only be explored, as empowering children with knowledge and skills related to nutrition and dietary habits, are likely to promote healthier eating behaviors from an early age ( 75 ).…”
Section: Discussionmentioning
confidence: 99%